Ama Samawa sebagai Media Pendidikan Karakter dalam Masyarakat Samawa - Wawan Hermansyah (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
Ama Samawa is a traditional proverb of the Samawa community that contains local wisdom values and functions as a guide for social behavior. This study aims to analyze Ama Samawa as a medium for character education in Samawa society through an examination of its denotative and connotative meanings. This research employs a descriptive qualitative approach using literature review and content analysis methods on 42 Ama Samawa proverbs. The findings indicate that Ama Samawa embodies character education values such as responsibility, honesty, hard work, justice, simplicity, self-control, and independence. These values are relevant to the social context of the Samawa community and are aligned with the objectives of national character education. Therefore, Ama Samawa has significant potential to be utilized as a character education medium based on local culture, both within family and community settings as well as in formal education